(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There is no doubt that the inspection is a dynamic process that is resorted to by the expert of this way and took a path in which he sought to reveal the hidden signs and symbols that needed attention in checking its texts which concealed by time until they have the opportunity to appear and be exposed. This study that I presented contains two important assets upon which such studies are based, namely: the study and the inspection. It is a manuscript named «Al-Nubtha mn E’lm Al-Balagah wa Tawabiu’ha», written by Shaikh Zain Al-Din Abdul-Rahim Al-Abanasi Al-Shafiq’i (May God have mercy on him). This book traces the arts of rhetoric and their artistic and taste paths. The joy of inspection comes through the correct verification of the text as it was written. It also contributes to supplementing the library with the heritage of the ancestors, so that it can be accessible to those interested and be useful in its content. This research came in two parts: the first part is a study on the author and the book, and the second part devotes it to the verified text. As well as research results and a list of resources and references.